Penerapan Pembelajaran STEAM Dalam Mengembangkan Kreativitas Anak Usia Dini: Pembelajaran STEAM, Kreativitas Anak Usia Dini - Sudarti Sudarti; Yuniarti Yuniarti; Widia Elanti Widia (Jurnal Kajian Anak (J-Sanak), 2024)
Science, Technology, Engineering, Art and Mathematics (STEAM) learning is considered as learning that can improve children's creative thinking. STEAM can be defined as a learning program design aimed at developing the ability to think critically, analytically, creatively and as a whole in studying a learning topic by children. This study aims to develop children's creativity by applying STEAM learning. This study uses Quantitative Research Experiment Design One Group Pre-test Post-test in which the pre-test is carried out at the beginning then continued with treatment 3 times and then ends with the final step, namely the post-test which has its own activities. The application of STEAM Learning is proven to be able to develop children's creativity with the results of SPSS significant value (2-tailed) 0.000 <0.05 with statistically tested data the result is t count> t picture, then Ho "rejected" and Ha "accepted". The hypothesis in this study means that there is a significant difference between the creativity of children aged 5-6 years before / after STEAM learning is applied to class B children totaling 21 children at UMP Model Lab Kindergarten, South Pontianak.